1992
DOI: 10.1002/jid.3380040106
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the imf on government expenditures: A study of african LDCs

Abstract: This paper examines the impact of IMF programmes on government expenditure allocations in African LDCs since the late 1970s. There was no obvious impact on expenditure by major economic function; for expenditure by type, only subsidies changed significantly as a proportion of central government expenditure. A more detailed analysis of military expenditure found that it was more likely to be cut in countries involved with the IMF. Possibly, the economic weaknesses which drove some countries to the IMF also caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 6 publications
(3 reference statements)
1
4
0
Order By: Relevance
“…The World Bank (1994) found that when African countries lowered their budget deficits from 1981-86 to 1990-91, "most of the cuts were in capital spending" (p. 47). Harris and Kusi (1992) reach similar conclusions for a selected group of African countries. 7 We do know in reality that the composition of the net capital inflows account is very heterogeneous.…”
Section: (6)supporting
confidence: 76%
“…The World Bank (1994) found that when African countries lowered their budget deficits from 1981-86 to 1990-91, "most of the cuts were in capital spending" (p. 47). Harris and Kusi (1992) reach similar conclusions for a selected group of African countries. 7 We do know in reality that the composition of the net capital inflows account is very heterogeneous.…”
Section: (6)supporting
confidence: 76%
“…Further, against the critique that adjustment programs hurt the poor, Ferroni and Kanbur find no evidence to support this. On the contrary, the authors show that the average share of discretionary and real per capita expenditures for twenty African countries on education, health and agricultural services have actually risen'(if modestly) over the period 1980-87 (see also Harris and Kusi, 1992).…”
Section: Social Sectorsmentioning
confidence: 98%
“…The authors also show that program coun tries have relied more heavily than nonprogram countries on cuts in military spending to implement fiscal adjustment. See also Harris and Kusi (1992) for evidence of lower mili tary spending in African countries with IMF-supported programs.…”
Section: Does Conditionality In Adjustmentmentioning
confidence: 99%